2018
DOI: 10.34050/jib.v6i1.4317
|View full text |Cite
|
Sign up to set email alerts
|

The Address Terms in English and Selayerese: a Sociolinguistic Perspective

Abstract: This research aims to reveal the use of address terms in English and Selayarese based on situation and context and to understand the aspects that influenced the use of address terms in English and Selayarese. This study was analyzed through descriptive qualitative approach. The English data were taken from some conversational events in the movies while the Selayarese data were taken from the participant observation, depth interview, and field notes. The data requirement is focused on the address terms performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Cultural transmission becomes significant in supporting the idea. Yule (in Zavitri, 2018) acknowledges that people have learned a certain language and a systemic order and add their own experience. The own experience mentioned in the statement is a cultural background itself.…”
Section: Resultsmentioning
confidence: 99%
“…Cultural transmission becomes significant in supporting the idea. Yule (in Zavitri, 2018) acknowledges that people have learned a certain language and a systemic order and add their own experience. The own experience mentioned in the statement is a cultural background itself.…”
Section: Resultsmentioning
confidence: 99%
“…Sex is a biological trait and gender is a social trait, where sex is biologically constructed and gender is socially and culturally constructed (Niraula, 2021;Silaban & Afriana, 2020). The influence of sex was found in the use of address terms which showed the difference between male and female particularly for the address terms of kinship, title, first name, intimacy relationship, and pronouns (Andikha & Ambalegin, 2022;Zavitri et al, 2018). For example; beli or bli was an address term for a man meanwhile mbok, adi, and iluh were the address terms for a woman.…”
Section: Discussionmentioning
confidence: 99%
“…Social status is a position or position that is owned by a person in a social group of people. The social status factor was found respect name since it was used to address the people who talked in the public, for instance; guru was referred to the person who had social religious status in the village (Suyana et al, 2022;Zavitri et al, 2018). The official position of the interlocutor in the second person was also the social factor influencing the address terms used in Menyali village which indicated that there was an interaction between speakers and hearers.…”
Section: Discussionmentioning
confidence: 99%
“…The way a person speaks will be greatly influenced by the context that accompanies the conversation, so that different language variations are created depending on the context (Caterine et al, 2021;George & Mamidi, 2020;Zavitri et al, 2018). Sociolinguistics occurs in multicultural societies where language is used in accordance with racial and cultural provisions (Bayyurt, 2016;Fitriani, 2017;Paradis & Nicoladis, 2007).…”
Section: Introductionmentioning
confidence: 99%